Les Éternels - Vandeweerd, Pierre-Yves (Belgium France, 2017)
This film is a story of wanderings and leaks on the borders of Nagorno-Karabakh, an Armenian enclave in Azerbaijan. Inhabited by the ghosts of the genocide and the war that has raged there for more than twenty years, the characters who go through this film carry within them the melancholy of the eternal.
Verzio Film Festival Submission
Keywords: Documentary films